The intervention and financing mechanisms of the EMS and the role of the ECU - MICOSSI, S. (PSL Quarterly Review, 2013)
The European Monetary System (EMS) embodies an agreement that national currencies in participating countries will be managed so as to maintain an agreed parity with other currencies. Although some flexibility is allowed, essentially governments must ensure that parities are maintained. The problem with the agreement is that there is no explicit statement as to how intervention on foreign exchange markets to maintain parity should be carried out. The author considers the background to the development of the EMS and examines how the parity agreement will allow the European Currency Unit to develop to a true international currency. JEL: E42, F31, F36